KETERBUKAAN DIRI PEREMPUAN PENGGUNA APLIKASI KENCAN ONLINE (BUMBLE) - Nabila Azzahra (2022)
The phenomenon of online dating applications has developed rapidly in society. Online dating apps are one of the new media developments. One of the online dating applications that is widely used by the Indonesian people is the online dating application Bumble. The online dating app Bumble is an app that offers a way to find friendships or romances that can connect all over the world and is said to be a "girl friendly" app because the Bumble online dating app has a unique feature that the female user has to start a conversation first. The purpose of this study was to find out how self-disclosure on the online dating application Bumble creates close relationships with new people. The theory that is relevant to this research is the theory of self-disclosure. This study uses a qualitative method with a phenomenological approach. The informants in this study were female users of the online dating application Bumble. The data analysis technique used in this research is the analytical technique developed by Moustakas. The results of this study were analyzed using several stages of self-disclosure, namely each informant has different levels and stages of self-disclosure and not all informants reach the deepest stage. At the start of the self-disclosure process, intimacy doesn't occur, especially with the online dating app Bumble.